UKURAN PERUSAHAAN, PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2008 – 2010 - Hayu Wikan Kinasih; Anna Sumaryati (MEDIA, 2012)
The emergence of Corporate Social Responsibility (CSR) is inseparable from the philosophical shift in management business entity organization. CSR disclosure is a communication process of the social and environmental impacts from economic activities of the organizationâ€™s special interest groups (stakeholders) and society as a whole. The purpose of this research is to understand the influence of company size, profitability and financial leverage towards corporate social responsibility disclosure. Independent variable in this research using the proxy Total Asset for company size, Earning Per Share for profitability, and Debt to Equity Ratio for financial leverage. The dependent variable of this research is corporate social responsibility disclosure using the proxy CSR Index.Sample of this research consist ofÂ 17 manufacturing company listed in Indonesian Stock Exchange over three years ie 2008-2010 with a total of 51 samples. This research found that partially company size (Total Asset) significantly influence the CSR disclosure which has sig. 0,014. Profitability (EPS) and Financial Leverage (DER) has sig. 0,248 and 0,196, so that there are no significant influence between Profitability and Financial Leverage towards CSR disclosure. Simoultaneously, independent variable (company size, profitability, and financial leverage) significantly influence dependent variable (CSR disclosure) which has sig. 0,001.